Navigating the Digital Era with Emotional Intelligence (Global Journal of Human-Social Science, 2025)
In today s digital era the pervasive integration of technology into daily life has raised questions about its influence on fundamental aspects of human behavior and cognition Technology is becoming more widely acknowledged for its potential to help students develop their emotional intelligence EI in addition to making the material easier to obtain and improving academic skills Emotional intelligence often referred to as EQ encompasses the ability to recognize understand and manage one s own emotions as well as the emotions of others This paper aims to investigate the relationship between technology use and Emotional Intelligence EI a crucial component of human social and emotional functioning Through a comprehensive review of existing literature technology can provide opportunities for enhancing certain aspects of emotional intelligence such as empathy and social awareness it also presents challenges that may impede its development The research article provides a comprehensive understanding of how technology may influence the development expression and regulation of emotions in individuals
Keywords: ducation; technology; emotional intelligence; social media; virtual reality; artificial intelligence